CGIAR-ISEAL Scoping Study: State of gender integration among ISEAL members in agri-food sectors - Morgan, Miranda (2022)
In 2022, CGIAR's HER+ initiative researchers partnered with ISEAL to explore how sustainability systems are able to contribute to advancing gender equality and women’s empowerment. Gender is a crosscutting theme in ISEAL’s strategic priority to power solutions to sustainability challenges. This partnership provides an opportunity for ISEAL to be more gender transformative in their thinking and approaches to solutions, and builds on their past work on gender. Specifically, the scoping study aimed to: explore how ISEAL members seek to enhance gender equality and women’s empowerment, with a focus on schemes in the agri-food sector; identify enabling factors and challenges for enhancing gender equality and promoting women’s rights and empowerment through ISEAL members’ systems; and consider opportunities for learning and collaboration to advance gender equality through VSS.